Developing fish feeder system using Raspberry Pi - Hidayatul Nur, Hasim; Ramalingam, Mritha; Ernawan, Ferda; R., Puviarasi (IEEE, 2017)
The Fish owners of the pet fish are usually distressed when they are away from home environment because they could not feed the fish on time. Both reasons, food starvation and overfeeding risk the health of fish and leads to poor water quality in indoor fish tanks. Thus monitoring the fish feeder is of great importance which can be very beneficial for the fish owners. This work is aimed to design a fish feeder system using microcontroller and Raspberry Pi based web application to relax the distressed fish owners in feeding their fish on time. This system is designed to overcome the problem of fish dying due to fish feeder malfunction. With this design, the fish owner can monitor the fish tank for correct functioning of the fish feeder. Also, the user can set schedules for feeding the fish through the web application.